If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.4(2x + 6) + 0.1 = 0.5(2Z + -3) Reorder the terms: 0.4(6 + 2x) + 0.1 = 0.5(2Z + -3) (6 * 0.4 + 2x * 0.4) + 0.1 = 0.5(2Z + -3) (2.4 + 0.8x) + 0.1 = 0.5(2Z + -3) Reorder the terms: 2.4 + 0.1 + 0.8x = 0.5(2Z + -3) Combine like terms: 2.4 + 0.1 = 2.5 2.5 + 0.8x = 0.5(2Z + -3) Reorder the terms: 2.5 + 0.8x = 0.5(-3 + 2Z) 2.5 + 0.8x = (-3 * 0.5 + 2Z * 0.5) 2.5 + 0.8x = (-1.5 + 1Z) Solving 2.5 + 0.8x = -1.5 + 1Z Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.5' to each side of the equation. 2.5 + -2.5 + 0.8x = -1.5 + -2.5 + 1Z Combine like terms: 2.5 + -2.5 = 0.0 0.0 + 0.8x = -1.5 + -2.5 + 1Z 0.8x = -1.5 + -2.5 + 1Z Combine like terms: -1.5 + -2.5 = -4 0.8x = -4 + 1Z Divide each side by '0.8'. x = -5 + 1.25Z Simplifying x = -5 + 1.25Z
| 2(x+y)+6n(x+y)= | | 49x^2+4=28 | | 0=-1.66x+79.21 | | 0=-1.66+79.21 | | 10a-11=5a+4 | | .5w+90=4w+90 | | 18x-6=22x-78 | | f(3)=3n | | 10r=9r+18 | | 4-k=-4 | | 0.5(2.5x+4)=6x+4 | | f(2)=3n | | -7x+5x-9x=-22 | | 6w-14=3w+4 | | 180(30-2)=s | | 16x^2+3x-124=0 | | 3-4x=10(x+1) | | 11=1y+2 | | 6(x+8)=63 | | b^2+16b+26=-3 | | x^2+y^2+2x+14y+50=0 | | 0.50x+0.05(10-x)=0.10(-31) | | y=(6-x)(7-6x) | | 2(m-7)=42 | | 11-7+x=3-2x-11 | | 6-v=5(v+6) | | 3(7x-5)=27x-87 | | 110=2x+48 | | 3*3.5+88=124 | | 87=4u+11 | | x+19+4x=-47-4x-51 | | 12x+82=124 |